Flexible MnS–Carbon Fiber Hybrids for Lithium‐Ion and Sodium‐Ion Energy Storage. Issue 51 (10th August 2018) - Gao, Shuang; Chen, Gang; Dall'Agnese, Yohan; Wei, Yingjin; Gao, Zhongmin; Gao, Yu
Abstract: Nanostructures can improve battery capacity and cycle life, especially with sulfide electrodes. In this work, a freestanding flexible electrode, consisting of MnS nanoparticles embedded onto carbon nanofibers, was prepared by electrospinning. The produced hybrid was used as an electrode for lithium‐ion and sodium‐ion batteries. MnS nanoparticles have a size of about 5 nm and the particles are evenly distributed in the carbon nanofibers. Carbon nanofibers act as electronic conductors and buffer the volume change, while MnS nanoparticles react through rapid electrochemical reaction. As a Li‐ion battery anode, this hybrid electrode exhibits specific capacities from 240 mAh g −1 at a high current density of 5 A g −1, up to 600 mAh g −1 at 200 mA g −1 . Abstract : Hybrid theory : A freestanding flexible electrode, consisting of MnS nanoparticles embedded onto carbon nanofibers, was prepared by electrospinning. The produced hybrid was used as an electrode for lithium‐ion and sodium‐ion batteries. Good rate performances were observed, attributed to an open 3D architecture.